Separation and Preconcentration of Gold, Silver and Palladium from Some Aluminum and Manganese Salts on Activated Carbon Column - Soylak, M.; Elci, L.; Narin, I.; Dogan, M. (Asian Journal of Chemistry, 2010)
A simple method for preconcentration and separation of trace amounts of gold, silver, palladium in some aluminium and manganese salts was established by using mini column filled activated carbon prior to their atomic absorption spectrometric determinations. The dithiophosphoric acid O,O-diethyl ester complexes of the analyte ions were adsorbed on the activated carbon column and desorbed with 2M NH3 in acetone. The effects of aluminium and manganese ions as interferent were discussed. The method was successfully applied for the determination of Au, Ag and Pd contents of some aluminium and manganese salts (recoveries> 95%, relative standard deviations < 10%).